Implementasi Model Lagu dalam Peningkatan Pemahaman Materi Bahasa Arab (Studi Eksperimen pada Siswa Madrasah Tsanawiyah Yapis Pattiro Bajo) - Hudri, Mawaddah; Sopian, Asep; Nursyamsiah, Nunung (IAIN Bone, 2021)
The article presented in the findings of this study aims at two main things, first, to determine the form of a song model in teaching Arabic at Madrasah Tsanawiyah Yapis Pattiro Bajo, Bone, South Sulawesi. Second, to determine the effect of implementing the song model in increasing students' understanding of Arabic language materials. The song model as an independent variable and model while Student Understanding is the dependent variable. The type of research used in this research is field research using a descriptive quantitative approach with the method of questionnaires, interviews, and observations. The sample in this study were students who studied Arabic in class VII (seven), namely as many as 85 people. From the results of this study, it can be concluded, 1) by applying the song model in learning Arabic, students become motivated to learn, feel happy and study with enthusiasm, and increase student activity. 2) there is a relevant relationship between the application of the song model with the level of understanding of Arabic learning material.